Receipt of pharmacotherapy for opioid use disorder by justice-involved U.S. Veterans Health Administration patients. (1st March 2016) - Finlay, Andrea K.; Harris, Alex H.S.; Rosenthal, Joel; Blue-Howells, Jessica; Clark, Sean; McGuire, Jim; Timko, Christine; Frayne, Susan M.; Smelson, David; Oliva, Elizabeth; Binswanger, Ingrid
Highlights: Receipt of pharmacotherapy for opioid use disorder may differ by justice status. Prison-involved veterans had a lower rate of receipt of pharmacotherapy. Jail/court- and non-justice-involved veterans did not differ in rate of receipt. Rates of receipt varied widely within VHA facilities by justice status. Abstract: Background: Pharmacotherapy – methadone, buprenorphine, or naltrexone – is an evidence-based treatment for opioid use disorder, but little is known about receipt of these medications among veterans involved in the justice system. The current study examines receipt of pharmacotherapy for opioid use disorder among veterans with a history of justice involvement at U.S. Veterans Health Administration (VHA) facilities compared to veterans with no justice involvement. Methods: Using national VHA clinical and pharmacy records, we conducted a retrospective cohort study of veterans with an opioid use disorder diagnosis in fiscal year 2012. Using a mixed-effects logistic regression model, we examined receipt of pharmacotherapy in the 1-year period following diagnosis as a function of justice involvement, adjusting for patient and facility characteristics. Results: The 1-year rate of receipt for pharmacotherapy for opioid use disorder was 27% for prison-involved veterans, 34% for jail/court-involved veterans, and 33% for veterans not justice-involved. Compared to veterans not justice-involved, those prison-involved had 0.75 lower adjusted odds (95% confidence interval [CI]: 0.65–0.87) of receiving pharmacotherapy whereas jail/court-involved veterans did not have significantly different adjusted odds. Conclusions: Targeted efforts to improve receipt of pharmacotherapy for opioid use disorder among veterans exiting prison is needed as they have lower odds of receiving these medications.